Microblog Content to Instill Care for Natural Environment Character in High School Students - Kyarto, Abdullah Fariz; Setyowati, Dewi Liesnoor; Hardati, Puji; Santoso, Apik Budi; Mahat, Hanifah (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
Instilling the character of caring for the natural environment in students is needed to increase awareness and active participation in natural conservation. With Instagram's popularity, microblog content has great potential to be used in instilling the character of caring natural environment more effectively. This study aims to explain the process of preparing environmental care microblog content, implementation on social media, and student responses to microblog content. With a quantitative approach and one-shot case study method, data collected through validation, tests, questionnaires, and documentation. The results showed that 1) The content preparation are considered very valid (material experts 90%, media experts 93%), 2) implementation on Instagram is designed to deliver messages effectively, and 3) student responses (cognitive, affective, conative) indicate that this content is able to provide understanding, motivation, and real encouragement to act caring for the environment. This indicates that microblog content contributes significantly to instilling environmental awareness in students.